2022
DOI: 10.1038/s44161-022-00155-0
|View full text |Cite
|
Sign up to set email alerts
|

GPR55 in B cells limits atherosclerosis development and regulates plasma cell maturation

Abstract: Dissecting the pathways regulating the adaptive immune response in atherosclerosis is of particular therapeutic interest. Here we report that the lipid G-protein-coupled receptor GPR55 is highly expressed by splenic plasma cells (PCs), upregulated in mouse spleens during atherogenesis and human unstable or ruptured compared to stable plaques. Gpr55-deficient mice developed larger atherosclerotic plaques with increased necrotic core size compared to their corresponding controls. Lack of GPR55 hyperactivated B c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Lack of GPR55 hyperactivated B cells, disturbed PC maturation and supported a possible relevance for complications in human atherosclerosis pathophysiology. 79 In conclusion, lipid metabolism interacts with B cells function.…”
Section: Lipid Metabolism Reprogramming Of Immune Cells In Acnementioning
confidence: 96%
“…Lack of GPR55 hyperactivated B cells, disturbed PC maturation and supported a possible relevance for complications in human atherosclerosis pathophysiology. 79 In conclusion, lipid metabolism interacts with B cells function.…”
Section: Lipid Metabolism Reprogramming Of Immune Cells In Acnementioning
confidence: 96%
“…The immune system, particularly immune cells such as T cells and B cells, has been identified as a critical modulator in this process. 81 Increasing evidence highlights the relevance of ferroptosis in various diseases characterized by immune infiltration like cancer, Alzheimer's disease, and autoimmune disorders. 82 Lei and colleagues have demonstrated that neurons undergoing ferroptosis could activate T cells and promote cytokine production in Th1 and Th17 cells via the regulation of ACSL4, which could be modulated by antiferroptotic compounds.…”
Section: T-cellmentioning
confidence: 99%
“…Phosphatidylglucose (PG) comprises a group of phospholipids with glucose as the hydrophilic head group, which has been found to anchor in the cell membrane and facilitate the transmembrane transport of various compounds. 11 The high-affinity receptor for lysophosphatidylglucose is G protein-coupled receptor (GPR55) and previous studies have shown that GPR55 in B cells limits atherosclerosis development and regulates plasma cell maturation, 12,13 which suggest that PG may against the development of atherosclerosis. However, the effect of dietary PG on atherosclerosis has not been reported.…”
Section: Introductionmentioning
confidence: 99%